An Exploration into “Do-It-Yourself” (DIY) CO2 Enrichment Chambers: Utilising Grey Oyster Mushroom (Pleurotus pulmonarius (Fr.) Quél) Respiration to Improve Okra (Abelmoschus esculentus L.) Seedlings Growth - Toh, Liang Su; Khor, Sen Chou; Kamaruzali, Muhammad Afiq; Jusoh, Mashitah; Muhamad Mujab, Azzami Adam; Khalid, Khalisanni; Fleming, Andrew; Yaapar, Nazmin (Malaysian Society of Plant Physiology, 2024)
The endeavour to employ CO2 from natural sources to improve plant growth is often challenging, especially in tropical climates. While mycelium bags from the mushroom industry can generate CO2, they need indoor conditions with controlled temperature, high humidity, and low light. These conditions are not present in open fields, leading to low CO2 production. Inspired by the ancient clay evaporative cooling device called the zeer pot, a new solution was developed to address this problem. The eventual design was a confinement chamber that housed the mycelium bags and the okra seedlings. The chamber conditions were sufficiently conducive for the mycelium bags to produce an ambient CO2 level of around 800 ppm during the day. The resulting okra seedlings under this high CO2 concentration of natural origin had a notable increase in overall biomass accumulation (+ 277%), carbon assimilation rate (+103%) as well as improved water use efficiency (+95%) compared to seedlings grown under ambient CO2 level. These promising findings not only proved the capability of mycelium as a natural CO2 generator but also as an additional economic potential for the farmers to gain income from the CO2-enriched crops as well as the harvested mushroom bodies at the time of mycelium bags maturity. Furthermore, this simple innovation opens the avenue for further interdisciplinary research in other agricultural efforts to improve crop yield and quality.